2017
DOI: 10.1111/dom.13159
|View full text |Cite
|
Sign up to set email alerts
|

Acute oral sodium propionate supplementation raises resting energy expenditure and lipid oxidation in fasted humans

Abstract: Short‐chain fatty acids (SCFAs), produced from fermentation of dietary fibre by the gut microbiota, have been suggested to modulate energy metabolism. Previous work using rodent models has demonstrated that oral supplementation of the SCFA propionate raises resting energy expenditure (REE) by promoting lipid oxidation. The objective of the present study was to investigate the effects of oral sodium propionate on REE and substrate metabolism in humans. Eighteen healthy volunteers (9 women and 9 men; age 25 ± 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
78
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(82 citation statements)
references
References 20 publications
4
78
0
Order By: Relevance
“…Canfora et al showed that colonic administration of SCFA mixtures (comprising acetate, propionate, and butyrate) increased fasting lipid oxidation and resting energy expenditure (REE) in overweight and obese subjects [48]. Further in vivo data from human cohorts has corroborated the finding that SCFAs raise whole-body REE and lipid oxidation [49], and shown these changes to be independent of fasting glucose and insulin levels [50]. Although mechanistic studies of these SCFA-induced effects are lacking in humans, current work suggests they provide significant improvements to oxidative metabolism that may translate into long-term benefits in weight control.…”
Section: The Microbiome In Energy Harvest and Expenditurementioning
confidence: 96%
“…Canfora et al showed that colonic administration of SCFA mixtures (comprising acetate, propionate, and butyrate) increased fasting lipid oxidation and resting energy expenditure (REE) in overweight and obese subjects [48]. Further in vivo data from human cohorts has corroborated the finding that SCFAs raise whole-body REE and lipid oxidation [49], and shown these changes to be independent of fasting glucose and insulin levels [50]. Although mechanistic studies of these SCFA-induced effects are lacking in humans, current work suggests they provide significant improvements to oxidative metabolism that may translate into long-term benefits in weight control.…”
Section: The Microbiome In Energy Harvest and Expenditurementioning
confidence: 96%
“…In humans, the distinct relation between SCFAs and the browning processes is less consistent. While some studies have highlighted beneficial effects of SCFA administration in terms of resting energy expenditure, fat oxidation or whole-body lipolysis, others have suggested that the beneficial effects depended on the basal fitness of individuals; some have even reported positive correlations between colonic SCFA levels and adiposity [111][112][113][114][115] . These conflicting results have yielded some potential deleterious effect of SCFAs.…”
Section: Shortmentioning
confidence: 99%
“…A number of research groups have therefore investigated the impact of administering SCFAs on weight gain to determine if the effects of a high-fibre diet can be replicated. Many of these studies have reported that administration of SCFAs promote improvements to long-term body weight by enhancing whole-body energy expenditure (Gao et al 2009, Hattori et al 2010, den Besten et al 2015, Canfora et al 2017, Chambers et al 2018. For energy expenditure to increase these would need to be a corresponding elevation in substrate oxidation; principally an increased contribution of lipid and/or carbohydrate oxidation to 'fuel' the enhanced energy demands.…”
Section: Introductionmentioning
confidence: 99%